A cost-effectiveness analysis of reslizumab in the treatment of poorly controlled eosinophilic asthma. (3rd August 2019) - Lam, Jenny; Hay, Joel W.; Salcedo, Jonathan; Kenyon, Nicholas J.
Abstract: Introduction : Poorly controlled severe eosinophilic asthma is difficult and costly to manage. Reslizumab, an add-on treatment for adults with severe eosinophilic asthma, reduces the number of exacerbations and improves the quality of life (QoL). The objective of this study was to evaluate the cost-effectiveness of reslizumab. Methods : A Markov model was used to compare the cost-effectiveness of add-on reslizumab with the standard-of-care (SOC) from the US societal perspective over a five-year time horizon. Efficacy and safety inputs for the model were based on data from two clinical trials (NCT01287039 and NCT01285323). Other model inputs, including mortality rates, costs, and utility, were estimated from literature, the Centers for Disease Control and Prevention (CDC), the US Department of Veterans Affairs (VA) and the Centers for Medicare and Medicaid Services (CMS). One-way, threshold, and probabilistic sensitivity analyses (PSA) were performed. Adherence, treatment response, and the placebo effect were evaluated in separate scenario analyses. Results : The base case incremental cost-effectiveness ratio (ICER) was 697 403 (2017 USD) per quality-adjusted life-years (QALYs). In the PSA, reslizumab becomes cost-effective in 50% of the iterations at a willingness-to-pay (WTP) threshold of 689 000. The model is most sensitive to the QoL improvement with reslizumab treatment in the one-way and threshold analyses. The response and adherence models had lower ICERs than the base model but still above 500 000. The ICER of the placebo effect model was 29 820. Conclusions : The improvement in QoL and exacerbation rates with reslizumab are associated with high costs, making reslizumab unlikely to be cost-effective at the 200 000 WTP threshold.